Capacited range coverage location model for electric vehicle charging stations: A case of Istanbul-Ankara highway - Tasdemir, Beste Desticioglu; Koc, Erdinc; Simsek, Ahmed Ihsan (Elsevier, 2025)
It is clear that the rate of use of electric vehicles is increasing day by day due to growing environmental concerns of consumers, scarcity of natural resources, increasing awareness of renewable energy sources, following technological progress, and the cost advantage it has for individual or corporate users. One of the most important drawbacks of electric vehicles is their low range. With the studies carried out in battery technology, it is aimed to increase the range distance. However, when the range distances of today's electric vehicles considered, vehicle owners demand to recharge as soon as possible on long distances. While electric vehicle owners have the opportunity to perform many activities during charging in the city, they do not have such opportunities in intercity traffic such as on highways. For this reason, the waiting times for charging stations on intercity roads should be reduced and their availability should be increased. In this study, the Istanbul-Ankara highway, one of the most frequently used highways in Turkey, is considered. It is aimed to reach the minimum number of charging stations that meet the assumptions. The capacited range coverage location model is used to solve a real-life problem by considering the distances between fuel stations and resting facilities on this highway. With the modifications made to the base model, the obtained model has become more suitable for use in real life problems. With the results obtained, it is stated in which gas station or resting facility charging stations should be installed on the highway.
Keywords: Electric vehicle; Location of charging station; Mathematical model; Range coverage location model; Highway network